Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the given quadratic equation, we will use algebraic manipulation and the method of solving quadratic equations. Here is a step-by-step solution:
Given equation:
[tex]\[ 4x^2 - 22 = x^2 + 5 \][/tex]
### Step 1: Move all terms to one side of the equation to set it equal to 0.
First, we need to move the terms from the right side of the equation to the left side. We do this by subtracting [tex]\(x^2\)[/tex] and 5 from both sides:
[tex]\[ 4x^2 - 22 - x^2 - 5 = 0 \][/tex]
### Step 2: Combine like terms.
Combine the [tex]\(x^2\)[/tex] terms and the constant terms:
[tex]\[ 4x^2 - x^2 - 22 - 5 = 0 \][/tex]
Simplify the equation:
[tex]\[ 3x^2 - 27 = 0 \][/tex]
### Step 3: Solve the quadratic equation [tex]\(3x^2 - 27 = 0\)[/tex].
First, add 27 to both sides to isolate the term involving [tex]\(x^2\)[/tex]:
[tex]\[ 3x^2 = 27 \][/tex]
Next, divide both sides by 3 to solve for [tex]\(x^2\)[/tex]:
[tex]\[ x^2 = 9 \][/tex]
### Step 4: Take the square root of both sides to solve for [tex]\(x\)[/tex].
[tex]\[ x = \pm\sqrt{9} \][/tex]
Since the square root of 9 is 3, we have:
[tex]\[ x = \pm 3 \][/tex]
Therefore, the solutions to the quadratic equation are:
[tex]\[ x = 3 \][/tex]
[tex]\[ x = -3 \][/tex]
### Conclusion:
The solutions to the quadratic equation [tex]\(4x^2 - 22 = x^2 + 5\)[/tex] are:
[tex]\[ x = 3 \][/tex]
[tex]\[ x = -3 \][/tex]
Given equation:
[tex]\[ 4x^2 - 22 = x^2 + 5 \][/tex]
### Step 1: Move all terms to one side of the equation to set it equal to 0.
First, we need to move the terms from the right side of the equation to the left side. We do this by subtracting [tex]\(x^2\)[/tex] and 5 from both sides:
[tex]\[ 4x^2 - 22 - x^2 - 5 = 0 \][/tex]
### Step 2: Combine like terms.
Combine the [tex]\(x^2\)[/tex] terms and the constant terms:
[tex]\[ 4x^2 - x^2 - 22 - 5 = 0 \][/tex]
Simplify the equation:
[tex]\[ 3x^2 - 27 = 0 \][/tex]
### Step 3: Solve the quadratic equation [tex]\(3x^2 - 27 = 0\)[/tex].
First, add 27 to both sides to isolate the term involving [tex]\(x^2\)[/tex]:
[tex]\[ 3x^2 = 27 \][/tex]
Next, divide both sides by 3 to solve for [tex]\(x^2\)[/tex]:
[tex]\[ x^2 = 9 \][/tex]
### Step 4: Take the square root of both sides to solve for [tex]\(x\)[/tex].
[tex]\[ x = \pm\sqrt{9} \][/tex]
Since the square root of 9 is 3, we have:
[tex]\[ x = \pm 3 \][/tex]
Therefore, the solutions to the quadratic equation are:
[tex]\[ x = 3 \][/tex]
[tex]\[ x = -3 \][/tex]
### Conclusion:
The solutions to the quadratic equation [tex]\(4x^2 - 22 = x^2 + 5\)[/tex] are:
[tex]\[ x = 3 \][/tex]
[tex]\[ x = -3 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.